Different Prevalence of Alarm, Dyspeptic and Reflux Symptoms in Patients with Cardia and Non-cardia Gastric Cancer - Franck, Caspar; Zimmermann, Nadja; Goni, Elisabetta; Lippert, Hans; Ridwelski, Karsten; Kruschewski, Martin; Kreuser, Nicole; Lingohr, Philipp; Schildberg, Claus; Vassos, Nikolaos; Waidmann, Oliver; Peitz, Ulrich; et al. (Journal of Gastrointestinal and Liver Diseases, 2021)
Background & Aims: Symptoms of patients with gastric cancer (GC) are often unspecific and differences in symptoms between patients with cardia and non-cardia GC have been poorly investigated. We aimed to characterize symptoms of patients with cardia and non-cardia GC. Methods: Patients with cardia (Siewert type II and III) and non-cardia GC were recruited in the German multicenter cohort of the Gastric Cancer Research (staR) study between 2013 and 2017. Alarm, dyspeptic and reflux symptoms at the time of presentation were documented using a self-administered questionnaire. Results: A completed self-administered questionnaire was available for 568/759 recruited patients (132 cardia GC, 436 non-cardia GC, male 61%, mean age 64 years). Dyspeptic symptoms were more common in patients with non-cardia GC (69.0 vs. 54.5%, p=0.0024). Cardia GC patients reported more frequently alarm symptoms (69.7 vs. 44.7%, p<0.0001), and were more likely to have Union for International Cancer Control (UICC) stage III-IV (54.1vs. 38.9%, p=0.0034). Especially, dysphagia and weight loss were more common in patients with cardia GC (49.2 vs. 6.4 %, p<0.0001 and 37.1 vs. 25.7%, p=0.02, respectively). No differences between the two groups were observed with respect to reflux symptoms. Patients with alarm symptoms were more likely to have UICC stage III-IV at presentation (69.4 vs. 42.9%, p<0.0001). Conclusions: In clinical practice the symptom pattern at presentation may serve as a hint for tumor localization. Despite the fact that they are common in the general population, dyspeptic symptoms offer a chance for earlier GC detection. Thus, in patients with dyspeptic symptoms who fail empiric approaches, endoscopy should not be delayed.
CRIS-Team WoS Importer:2022-01-07